Exploring The Multimodal Integration of Emerging Transit ‎Systems in Urban Mobility - Rahman, Dr. F; Mishra , Dr. Nidhi (International Journal of Basic and Applied Sciences, 2025)
This research investigates the integration methods for new transit systems within urban mobility frameworks when studying multi-modal ‎transportation systems. Cities that grow face significant obstacles from transportation system congestion, alongside pollution and ‎overall operational inefficiency. Researchers explore the possibility of building integrated transportation systems by bringing together ‎autonomous vehicles with electric scooters and bike-sharing systems, along with public transit and ride-sharing services, to create efficient, ‎sustainable urban mobility frameworks. This study explores multi-modal integration from technical and policy perspectives using a combined ‎qualitative case study and quantitative modeling methods. Effective implementation of transportation integration efforts produces benefits ‎that include reduced congestion and decreased carbon pollution, together with enhanced mobility throughout cities. Finally, the research ‎proposes methods for lawmakers and municipal planners to implement interconnected multi-modal transportation systems that will meet ‎shifting urban mobility requirements‎.